2002
DOI: 10.1021/ic020508y
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer Study of Reduced Rubredoxin As Purified and in Whole Cells. Structural Correlation Analysis of Spin Hamiltonian Parameters

Abstract: The [Fe(II)(Cys)(4)](2-) site of rubredoxin from Clostridium pasteurianum (Rd(red)) has been studied by Mössbauer spectroscopy in both purified protein and whole cells of Escherichia coli overproducing it. Excellent fits were obtained to an S = 2 spin Hamiltonian for D = 5.7(3) cm(-1), E/D = 0.25(2), delta = 0.70(3) mm/s, DeltaE(Q) = -3.25(2) mm/s, eta = 0.75(5), A(x) = -20.1(7) MHz, A(y) = -11.3(2) MHz, and A(z) = -33.4(14) MHz. These parameters were analyzed with crystal-field theory for the (5)D manifold of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
71
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 36 publications
9
71
0
1
Order By: Relevance
“…Such excited states can be admixed into the ground state by spin-orbit coupling, and this admixture would affect the D value but would not lead to a reduction of A x and A y . It has recently been shown that 40% of the zero-field splitting of the S ϭ 2 state of Fe II rubredoxin is attributable to mixing with excited S ϭ 1 configurations and that such mixing does not affect the A tensor (50).…”
Section: Methodsmentioning
confidence: 99%
“…Such excited states can be admixed into the ground state by spin-orbit coupling, and this admixture would affect the D value but would not lead to a reduction of A x and A y . It has recently been shown that 40% of the zero-field splitting of the S ϭ 2 state of Fe II rubredoxin is attributable to mixing with excited S ϭ 1 configurations and that such mixing does not affect the A tensor (50).…”
Section: Methodsmentioning
confidence: 99%
“…It must be noted that spin-Hamiltonian parameters are also sensitive to the S-Co-S angles. In fact it has been shown, that even for the JT active [Fe(SPh) 4 ] 2-complexes simple A c c e p t e d M a n u s c r i p t ligand field arguments that would stabilize the elongated or compressed geometries cannot explain the experimentally observed Mössbauer parameters [169,170]. In fact the SH parameters of such iron centers were found to be rather sensitive to more complicated patterns of distortion such as those described by the variation of the S-Fe-S-R torsion angles.…”
Section: Non-degenerate Ground Statesmentioning
confidence: 99%
“…2a) in the ½Fe 2þ a Fe 3þ b and ½Fe 3þ a Fe 2þ b localizations. The x a , y a , z a (x b , y b , z b ) axes are directed along the edges of the cube in which the Fe a S 4 (Fe b S 4 ) tetrahedra is inscribed [36,57,59]; z a kZ and z b k(ÀZ) are directed perpendicular to the common S-S edge, X-axis (Fig. 4 in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[52]). For the Fe 2+ ion, we consider a distortion, which compresses the tetrahedron along the local z a and z b (and cluster Z) axes and results in the non-degenerate 5 A 1 ðd z 2 Þ ground state [36,57,59] in the localized states. The ground state Slater determinant wave functions w 0 ð 5 A 1 ;mÞðFe 2þ Þ and u 0 ( 6 A 1 , m)(Fe 3+ ) are the following [36,37]: [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation